The Influence of Human Relations, Physical Conditions of the Environment on the Work Ethic of Nurses in the Inpatient Installation of Harapan Dan Doa Hospital, Bengkulu City - Herlina Herlina; Endang Komara; Budi Santoso (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to describe the variables of human relations, physical conditions of the environment, and work ethic and to see the influence of human relations, physical conditions of the environment on the work ethic of nurses in the Inpatient Installation of Harapan and Doa Hospital, Bengkulu City. The research design used by the author in this study is a quantitative method. The sample in this study was taken from the entire population, namely 91 nurses in the Inpatient Installation of Harapan and Doa Hospital, Bengkulu City. The data analysis of this study used multiple linear regression tests with the SPSS program. The results of the study showed that partially there was a positive and significant influence between human relations on work ethic. This means that if the human relations variable is increased, the nurse's work ethic will increase in line with the increase in nurse human relations, partially there is no influence between the physical conditions of the environment on work ethic. This means that if the physical conditions of the environment are increased, the nurse's work ethic does not increase, and simultaneously there is an influence of human relations and physical conditions of the environment on the nurse's work ethic with a percentage contribution of 38.5% and the remaining 61.5% is influenced or explained by other variables that are not included in the model or outside of this study.